A novel small‐angle neutron scattering detector geometry. (3rd July 2013) - Kanaki, Kalliopi; Jackson, Andrew; Hall‐Wilton, Richard; Piscitelli, Francesco; Kirstein, Oliver; Andersen, Ken H.
Abstract : A novel 2π detector geometry for small‐angle neutron scattering (SANS) applications is presented and its theoretical performance evaluated. Such a novel geometry is ideally suited for a SANS instrument at the European Spallation Source (ESS). Motivated by the low availability and high price of 3 He, the new concept utilizes gaseous detectors with 10 B as the neutron converter. The shape of the detector is inspired by an optimization process based on the properties of the conversion material. Advantages over the detector geometry traditionally used on SANS instruments are discussed. The angular and time resolutions of the proposed detector concept are shown to satisfy the requirements of the particular SANS instrument.